Macrobenthos and Water Quality of Langat River System, Malaysia - Mohamed Zawawi, Azrina (2002)
A study on macrobenthos and water quality of Langat River system was conducted at 12 sampling stations in Langat River and its tributaries. Semenyih River. Chongkak. River and Lopo River. Samples were collected every month from March 1998 to February 1999 except for September 1998 and December 1998. Ten taxa of macrobenthos with 64 species were identified. Ephemeroptera and Diptera were dominant at the upstream area of Langat River system while Oligochaeta was dominant at the downstream area. OIigochaeta had the highest percentage of mean density (98.89%) followed by Diptera (0.57%) and Ephemeroptera (0.34%). Limnodrilus hoffmeister; from the order of Oligochaeta had recorded the highest mean density about hoffmeisteri from the class of Oligochaeta had recorded the highest mean density about 1899673.34 ind/m² (80%) and it was dominant at all the polluted stations in the downstream of Langat River. This species can be used as the bioindicator of the polluted water bodies in Malaysia.